The Effect of Warm Compress on Lowering Dysmenorrhea Pain - Wina Widianti; Yuliana Siti Nurazizah; Vina Nurkania; Aenun Fauzi; Aldi Hidayat; Yulistianto Herdiawan; Tian Septian Nugraha; Elis Roslianti (Genius Journal, 2021)
Introduction: dysmenorrhea occurs during the menstrual period which can be a gynecological problem characterized by lower abdominal pain, if the pain is not overcome and unbearable it can cause obstruction of normal activities to a sign of a reproductive disorder. Warm compress relaxation therapy is a nursing intervention that can reduce the pain scale in patients with dysmenorrhea. Objective: his study was conducted with the aim of proving the effectiveness of warm compresses on reducing the pain scale of dysmenorrhea and preventing activity barriers in STIKes Muhammadiyah Ciamis female students who are menstruating. Method: his study uses 2 time scale pain measurements, namely pre test and post test with a pre experimental design. The population in this study were 112 people with a total of 30 respondents using the accidental sampling technique along with inclusion and exclusion criteria. Statistical data analysis used the Wilxocon-non-parametric test with the SPSS version 20 application. Result: The pre-test measurement the majority of the pain scale suffered by respondents, namely scale 3 as many as 13 respondents (43.30%) and on the results of the post-test pain scale measurement or after being given a compress intervention warm majority decreased on a scale of 1 as many as 19 respondents (63.30). The results of the non-parametric Wilcoxon test showed a significant number of value < value or 0.000 < 0.05 which stated that there was a significant relationship between giving warm compress therapy to reducing the pain scale of dysmenorrhea. Conclussion: his significance value can be used as a reference for doing warm compress therapy to reduce the pain scale of dysmenorrhea with economical and low side effects.